Respuesta :

[tex]-3;-12;-48;-192;...\\\\It's\ the\ geometric\ sequence:a_n=a_1r^{n-1}\\\\a_1=-3;\ a_2=-12\\\\r=a_2:a_1\to r=-12:(-3)=4\\\\\boxed{a_n=-3\cdot4^{n-1}}\to\fbox{b.}[/tex]

Answer:

b)  [tex]a_{n} = (-3)4^{n-1}[/tex].

Step-by-step explanation:

Given :  -3, -12, -48, -192, ...

To find : find an equation for the nth term of the sequence.

Solution : We have given  -3, -12, -48, -192, ...

Nth term of geometric sequence = [tex]a_{n} = a_{1}r^{n-1}[/tex].

Where, [tex]a_{n}= nth terms[/tex].

[tex]a_{1}= first term[/tex].

r = common ratio.

r = [tex]\frac{second term}{first term}[/tex]

r =  [tex]\frac{-12}{-3}[/tex] .

r = 4.

[tex]a_{n} = (-3)4^{n-1}[/tex].

Therefore,b)  [tex]a_{n} = (-3)4^{n-1}[/tex].